Titanium dioxide/ silicon oxycarbide hybrid polymer derived ceramic as high energy & power lithium ion battery anode material - Pahwa, Saksham (Kansas State University, 2016)
Energy has always been one of the most important factors in any type of human or industrial endeavor. Clean energy and alternative energy sources are slowly but steadily replacing fossil fuels, the over-dependence on which have led to many environmental and economic troubles over the past century. The main challenge that needs to be addressed in switching to clean energy is storing it for use in the electrical grid and transportation systems. Lithium ion batteries are currently one of the most promising energy storage devices and tremendous amount of research is being done in high capacity anode and cathode materials, and better electrolytes and battery packs as well, leading to overall high efficiency and capacity energy storage systems. Polymer derived ceramics (PDCs) are a special class of ceramics, usually used in high temperature applications, but some silicon based PDCs have demonstrated good electrochemical properties in lithium ion batteries. The goal of this research is to explore a special hybrid ceramic of titanium dioxide (TiO₂) and silicon oxy carbide (SiOC) ceramic derived from 1,3,5,7 -- tetravinyl -- 1,3,5,7 -- tetramethylcyclotetrasiloxane (TTCS) polymer for use in lithium ion batteries and investigate the source of its properties which might make the ceramic particularly useful in some highly specialized energy storage applications.
Keywords: Lithium ion batteries; Automobile batteries; Polymer derived ceramics; Silicon oxy carbide; Titanium di oxide nanoparticles; Battery anode materials; Materials Science (0794); Mechanical Engineering (0548); Nanotechnology (0652)